FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN PEMBERIAN IMUNISASI TETANUS TOXOID PADA IBU HAMIL TRIMESTER III DI UPT PUSKESMAS SUMBANG KABUPATEN ENREKANG - Jumriani Jumriani; Resky Devi Akib; St. Nurbaya (Universitas Islam Madura, 2023)
Husband's knowledge, attitudes and motivation about TT immunization really help reduce maternal mortality, because knowing immunization will allow a pregnant woman to go to a health service more quickly so that care can be provided by a midwife to screen for this risk, namely early detection of complications. To find out the factors associated with the completeness of tetanus toxoid immunization in third trimester pregnant women at UPT Puskesmas Sumbang, Enrekang Regency. The research was conducted in May 2023. The population in this study were all pregnant women who had their pregnancies checked at the UPT Puskesmas Sumbang, Enrekang Regency. The sample in this study were 40 pregnant women in their third trimester at the UPT Puskesmas Sumbang, Enrekang Regency, using the accidental sampling technique. The results showed that there was a relationship between knowledge and TT immunization. The results showed that there was a relationship between attitude and TT immunization. The results showed that there was a relationship between motivation and TT immunization. It is expected that health workers, especially midwives, will provide information through counseling about tetanus toxoid (TT) immunization.